A General Method for Transition Metal Single Atoms Anchored on Honeycomb‐Like Nitrogen‐Doped Carbon Nanosheets. Issue 10 (31st January 2020) - Zhang, Xiaoyan; Zhang, Shan; Yang, Yong; Wang, Liguang; Mu, Zijie; Zhu, Haishuang; Zhu, Xiaoqing; Xing, Huanhuan; Xia, Hongyin; Huang, Bolong; Li, Jing; Guo, Shaojun; et al.
Abstract: Excavating and developing highly efficient and cost‐effective nonnoble metal single‐atom catalysts for electrocatalytic reactions is of paramount significance but still in its infancy. Herein, reported is a general NaCl template‐assisted strategy for rationally designing and preparing a series of isolated transition metal single atoms (Fe/Co/Ni) anchored on honeycomb‐like nitrogen‐doped carbon matrix (M1 ‐HNC‐T1 ‐T2, M = Fe/Co/Ni, T 1 = 500 °C, T 2 = 850 °C). The resulting M1 ‐HNC‐500‐850 with M‐N4 active sites exhibits superior capability for oxygen reduction reaction (ORR) with the half‐wave potential order of Fe1 ‐HNC‐500‐850 > Co1 ‐HNC‐500‐850 > Ni1 ‐HNC‐500‐850, in which Fe1 ‐HNC‐500‐850 shows better performance than commercial Pt/C. Density functional theory calculations reveal a choice strategy that the strong p–d‐coupled spatial charge separation results the Fe‐N4 effectively merges active electrons for elevating d‐band activity in a van‐Hove singularity like character. This essentially generalizes an optimal electronic exchange‐and‐transfer (ExT) capability for boosting sluggish alkaline ORR activity. This work not only presents a universal strategy for preparing single‐atom electrocatalyst to accelerate the kinetics of cathodic ORR but also provides an insight into the relationship between the electronic structure and the electrocatalytical activity. Abstract : A series of porous nitrogen‐doped carbon‐supported single‐atom electrocatalysts is developed via a facile NaCl template‐assisted strategy; the strong p–d‐coupled spatial charge separation of their M–N4 sites boosts the oxygen reduction activity.